Coculturing embryonic stem cells with damaged hepatocytes leads to restoration of damage and high frequency of fusion - Xu, D; Wang, F; Pan, Z; Guo, Q (Cellular and Molecular Biology, 2009)
Controversy surrounds issue of cell fusion as a repair mechanism whereby stem cells regenerate. To identify the ratio of fusion happens between stem cells and damaged cells, hepatic cells were damaged with 200Î¼M H2O2 for 2 hr. Then, mouse ESCs were cocultured with damaged human hepatocytes. Fusion was detected directly by karyotyping after 48hr coculture as well as by Oct4 promoter drove GFP signal. Results showed that average ratio of fusion in undamaged control group was 0.031 while ratio of fusion in damaged group was 0.357, which was 10 times higher than fusion happened in the control group. Meanwhile, GFP signal indicated that fusion induced hepatic cells' Oct-4 reactivation. Fusion derived hybrid cells contained chromosomes from both parental cells. Most of the chromosomes were from damaged human hepatic cells. Activity of damage-related enzymes LDH, SGOT and SGPT were significantly lower at 48hr coculture than at 12hr coculture. Expression of albumin in co-culture system was up-regulated after coculture, which indicated the reparation of damage after coculturing. Also, by applying RT-PCR and immunocytochemistry differentiation status of ES cells were evaluated. It was shown that ES cells differentiated to hepatic lineage cells and expressed hepatic genes and proteins.